Full-Thickness Skin Grafting in Nasal Reconstruction - Weathers, William M.; Bhadkamkar, Mohin; Wolfswinkel, Erik M.; Thornton, James F. (Seminars in Plastic Surgery, 2013)
Skin grafting in nasal reconstruction, long used by dermatologists, can provide superior results and can well be the “go to” procedure for nasal reconstruction. The upper two-thirds of the nose is composed of both flattened, featureless and often thin skin that is well recreated with defect-only full-thickness grafting. Skin grafting for the lower third of the nose has been practiced for years by dermatologists; over the last 4 to 5 years, it has been embraced by plastic surgeons. The patient and donor site selection is critical. Meticulous attention to graft selection, utilization of a no-touch technique during graft harvest and placement of surgical bolsters with through-and-through tacking sutures are essential to ensure 100% graft take and a successful aesthetic result.
Keywords: full-thickness skin graft; Mohs reconstruction; nasal defect